Flight activity and pollen resources of Apis nigrocincta and Apis cerana in Central Sulawesi, Indonesia - Raffiudin, Rika; Ariyanti, Nunik Sri; Aprilianingrum, Inayah; Anwar, Hairul; Shullia, Nurul Insani; Bening, Sri; Wiyati, Sri Yuliasih; Priawandiputra, Windra; Saleh, Shahabuddin; Suardi; Fahri, Fahri; Putra, Ramadhani Eka; et al. (Agriculture and Natural Resources, 2022)
Importance of the work: Apis nigrocincta and A. cerana are important pollinators in Sulawesi; however, their flight activity patterns remain unstudied. Objectives: To characterize the flight activity of A. nigrocincta and A. cerana bees and its relationship to environmental factors and pollen sources. Materials & Methods: The flight activity of both honey bee species in lowland Central Sulawesi was observed during 0700–1600 hours and correlations between flight activity and environmental factors were analyzed. Bee pollen was collected from the hind legs of returning bees. Pollen acetolysis and color analysis were conducted to identify pollen sources. Results: Flight activity was higher and pollen sources were more diverse in A. cerana than for A. nigrocincta. The latter only collected a single type of pollen from Cocos nucifera, which was the dominant pollen source for both species, indicating that environmental management is needed to ensure the sustainability of beekeeping with the native A. nigrocincta in the presence of the introduced A. cerana. A. cerana collected Gramineae pollen, with 12 pollen types from 9 families and 3 unidentified types of pollen. Bee pollen with a single predominant pollen type, such as C. nucifera, varied in color. General linear models revealed that light intensity and temperature negatively affected flight activity, in contrast to the results of other studies. Main finding: In the apiaries of Central Sulawesi, the more widely distributed and adaptable A. cerana had higher flight activity and collected a greater diversity of pollen compared with the Sulawesi native A. nigrocincta.